CHEMICAL EQUILIBRIUM IN THE PROPIONIC ACID - ETHANOL - ETHYL PROPIONATE - WATER SYSTEM AND EXTRACTION PROCESSES WITH PARTICIPATION OF DEEP EUTECTIC SOLVENTS - M. A. Toikka; A. A. Samarov; A. A. Sadaev; A. A. Senina; O. L. Lobacheva (Тонкие химические технологии, 2019)
New experimental data on the chemical equilibrium in the propionic acid - ethanol - ethyl propionate - water system at 293.15 K and atmospheric pressure are presented. Chemically equilibrium compositions corresponding to the liquid-liquid equilibrium were obtained by gas chromatographic analysis. Using the method of nuclear magnetic resonance, homogeneous chemically equilibrium compositions were determined and the concentration equilibrium constant is calculated. The surface of chemical equilibrium and the region of splitting chemically equilibrium compositions are represented in the square of the transformed concentration variables. Comparison of the data obtained in the work with the literature was carried out at 303.15 and 313.15 K. It was found that the region of such compositions decreases with increasing temperature, while the surface of chemical equilibrium does not change the shape and position in the concentration space in the temperature range 293.15-313.15 K and atmospheric pressure. Liquid-liquid equilibrium compositions have also been obtained by gas chromatographic analysis for ethanol and ethyl propionate in the pseudo-ternary system using deep eutectic solvents (DES) based on choline chloride and glycerol / urea in whole range of concentration. The analysis of the extraction properties of DES showed the highest efficiency of DES based on choline chloride and urea. Experimental data on phase equilibrium are processed using Othmer-Tobias and Hand models. The calculated correlation coefficient (more than 0.99) indicates a high internal consistency of the experimental data obtained in this work.